Direct Integration of Strained‐Pt Catalysts into Proton‐Exchange‐Membrane Fuel Cells with Atomic Layer Deposition. Issue 30 (10th June 2021) - Xu, Shicheng; Wang, Zhaoxuan; Dull, Sam; Liu, Yunzhi; Lee, Dong Un; Lezama Pacheco, Juan S.; Orazov, Marat; Vullum, Per Erik; Dadlani, Anup Lal; Vinogradova, Olga; Schindler, Peter; Tam, Qizhan; et al.
Abstract: The design and fabrication of lattice‐strained platinum catalysts achieved by removing a soluble core from a platinum shell synthesized via atomic layer deposition, is reported. The remarkable catalytic performance for the oxygen reduction reaction (ORR), measured in both half‐cell and full‐cell configurations, is attributed to the observed lattice strain. By further optimizing the nanoparticle geometry and ionomer/carbon interactions, mass activity close to 0.8 A mgPt −1 @0.9 V iR‐free is achievable in the membrane electrode assembly. Nevertheless, active catalysts with high ORR activity do not necessarily lead to high performance in the high‐current‐density (HCD) region. More attention shall be directed toward HCD performance for enabling high‐power‐density hydrogen fuel cells. Abstract : Designer electrocatalysts can be deposited via atomic layer deposition onto support structures for performance evaluation under various platforms. In this example, strained platinum catalysts are formed by dissolving cobalt oxide from the Pt/CoO x core–shell structure. Performance enhancement seen on the rotating disk electrode is validated in the membrane electrode assembly.